2019
DOI: 10.1111/jfpe.13049
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study and optimization of the extraction of Algerian date stones oil (Phoenix dactylifera L.) using supercritical carbon dioxide

Abstract: An experimental extraction of Algerian date stones oil was carried out using supercritical carbon dioxide. Response surface methodology was used to investigate the effect of pressure (150–250 bar), temperature (313–333 K) and particles diameter (0.3–0.9 mm) on the extraction yield. The comparison of the predicted results with the experimental values confirmed the reliability of this technique. The optimum yield value was determined around 14.26% and was obtained at a pressure of 250 bar, a temperature of 333 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…However, Takadas and Doker [68] showed that when the temperature is increased, the vapor pressure is increased as well, leading to a decrease in the density of CO 2 , which could decrease the oil yield. In another study done by Mehdi et al [75] on Algerian date seed oil extracted using the SC-CO 2 method, the effects of the different parameters (pressure, temperature, and particle size) on the extraction yield, as well as the fatty acid profile, were investigated. The results revealed that the pressure and the interaction between the pressure and temperature had a significant positive effect on the extraction yield of date seed oil.…”
Section: Supercritical Fluid Extraction (Sfe)mentioning
confidence: 99%
“…However, Takadas and Doker [68] showed that when the temperature is increased, the vapor pressure is increased as well, leading to a decrease in the density of CO 2 , which could decrease the oil yield. In another study done by Mehdi et al [75] on Algerian date seed oil extracted using the SC-CO 2 method, the effects of the different parameters (pressure, temperature, and particle size) on the extraction yield, as well as the fatty acid profile, were investigated. The results revealed that the pressure and the interaction between the pressure and temperature had a significant positive effect on the extraction yield of date seed oil.…”
Section: Supercritical Fluid Extraction (Sfe)mentioning
confidence: 99%
“…Our studies suggested that extraction temperature had a dual influence on the flaxseed oil yield during the SBE process. More specifically, on the one hand, the elevation of extraction temperature increased the rate of mass transfer 26 and elevated the solubility of the solute 27 , causing the improvement of extraction efficiency. On the other hand, the increase of temperatures reduced the density of extraction solvent and thus a reduction of dissolving capacity for oil 28 .…”
Section: Response Surface Analysismentioning
confidence: 99%
“…In addition, recent studies have put into evidence the antidiabetic potential of date seeds extract. ,, To the best of our knowledge, the date seeds oil (DS oil) has never been investigated for antidiabetic activity. Recently, we have carried out the extraction of date seeds oil by supercritical carbon dioxide as an alternative to organic solvent extraction processes . Indeed, Supercritical Fluid Extraction (SFE) is an innovative, clean, and environmentally friendly technique that has gained high concern over the traditional or conventional extraction ways like steam-distillation and solvent extraction due to the use of carbon dioxide (CO 2 ), an inert, nontoxic, nonflammable, and volatile solvent .…”
Section: Introductionmentioning
confidence: 99%